Social Media as an important element of sports organization external communication - Katarzyna Gajek (Nicolaus Copernicus University in Toruń, 2016)
There is one thing that significantly contributed to shape social processes in the last two decades - the emergence of social media, which teamed up external communication strategies of various types sports organizations. Sports organization is distinguished by not so much the structure or function of management but a product. Sport becomes a specific area of social life, which is characterized by the importance of interactions between the organization and its customer what makes the organizational external communication particularly significant. Through vary channels sports organization provides communication with the client as well as builds the basis for persistence of each sports organization. The important question appears referring to this issue about the way in which sports organizations use the latest communication technologies in the process of building relationships with customers and co-creating the product. The purpose of this article, however, is an attempt to understand why social media have become particularly attractive tool in building efficient communication sports organization with the customer. There are two framing research questions asked: 1. What is a social media ecosystem and what is the difference between ecosystem with functioning social media in it and without them? 2. Why the social media settled the communication process between vary sports organizations and theirs customers? The first part of the article descripts and analyses the social media ecosystem by focusing on the elements of this system and its distinctive qualities shaped by modern technology and cultural changes. There is an attempt made to explain the specific compound sports organizations and social media in the following part of the article. The author basing on the literature and examples of activities of selected organizations argues that the main elements relevant to the relationship of social media and sport are emotions, iconic communication, visuals, identity and narrative.